Cermin Diri dan Cermin Kristen: Dalam Membantu Seseorang Mengenali Diri Sendiri dan Mengembangkan Hubungan dengan Tuhan - Litri Yerisa Eribka; Yakub Fransisko; Saul Napat; Sarmauli Sarmauli (Jurnal Magistra, 2024)
The purpose of this research is to explore the role of self-mirrors and Christian mirrors in helping someone recognize themselves and develop a relationship with God. This research is qualitative research with data search techniques through secondary sources, namely through the latest journals as part of the latest research. The important findings of this research indicate that both types of mirrors can be an effective means of strengthening self-awareness and deepening one's spiritual connection with God, providing deeper insight into one's identity and strengthening spiritual beliefs. This research makes an important contribution to the understanding of how self-mirrors and Christian mirrors can be used as tools for self-development and spirituality.